1998
DOI: 10.1016/s0006-3495(98)77570-8
|View full text |Cite
|
Sign up to set email alerts
|

Voltage and Cosubstrate Dependence of the Na-HCO3 Cotransporter Kinetics in Renal Proximal Tubule Cells

Abstract: The voltage dependence of the kinetics of the sodium bicarbonate cotransporter was studied in proximal tubule cells. This electrogenic cotransporter transports one Na+, three HCO3-, and two negative charges. Cells were grown to confluence on a permeable support, mounted on a Ussing-type chamber, and permeabilized apically to small monovalent ions with amphotericin B. The steady-state, di-nitro-stilbene-di-sulfonate-sensitive current was shown to be sodium and bicarbonate dependent and therefore was taken as fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…As can be seen in Fig. 7, these results fit nicely to the concentration dependence published by Gross and Hopfer [16], indicating a Hill coefficient near 3.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As can be seen in Fig. 7, these results fit nicely to the concentration dependence published by Gross and Hopfer [16], indicating a Hill coefficient near 3.…”
Section: Discussionsupporting
confidence: 88%
“…In an elegant study Gross and Hopfer [16] demonstrated that the charge transport by rkNBC of primary monolayer cultures of rat proximal tubule exhibits a sigmoidal dependence on [HCO 3 -] i with a Hill coefficient near 3, which agrees with the flux coupling ratio of q=3:1 observed in the same preparation [15]. Although our measurements could not be completed, 1 we succeeded in changing [HCO 3 -] i from 17.5 to either 10.8 or 35.0 mmol/l in three patches bathed with 0.5 µmol/l [Ca 2+ ] i that exhibited q=3:1 (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake rate was insensitive to presumed depolarization by increasing extracellular [K + ] and it was suggested that this could reflect an electroneutral Na,HCO 3 -cotransport. As pointed out by Gross and Hopfer (124), the rate of an electrogenic transport is not necessarily strongly dependent on the membrane potential because the effect of the membrane potential depends on how the transport molecule operates, i.e. whether the rate limiting step of the translocation is voltage sensitive.…”
Section: The Precloning Eramentioning
confidence: 98%
“…The question of the kinetic model of the electrogenic Na,HCO 3 -cotransporter was investigated in a detailed study by Gross and Hopfer (124). Based on a comparison of experimental data and a model for ordered binding of Na + and HCO 3 − , it was concluded that an ordered model is possible and that the major voltage dependence of the transporter is associated with the binding and translocation of HCO 3 − , whereas the binding of Na + is voltage independent.…”
Section: The Precloning Eramentioning
confidence: 99%